Effect of Magnetic Field Coupled Deep Cryogenic Treatment on Wear Resistance of AISI 4140 Steel - Liang Tang; Xianguo Yan; Yijiang Jiang; Fan Li; Haidong Zhang (Advances in Materials Science and Engineering)
In this study, a new magnetic field coupled deep cryogenic treatment (MDCT) is developed and its effect on wear resistance of AISI 4140 steel is investigated. Compared with wear resistance of untreatment (UT), wear resistance of MDCT increases by 29%. Wear resistance is inversely proportional to the friction coefficient. The treatment promotes the phase transformation and dislocation movement to generate more martensite in multidirectional distribution and optimized carbide. It enhances material property and repairs surface defect. Moreover, the wear mechanism of MDCT is only abrasive wear in the form of microscopic cutting, while other process groups are oxidative wear and abrasive wear in the form of microscopic cutting and microscopic fracture.